Natural Increase in Bali Cattle Population in the District Kabawo, Muna Regency - Andiwea Andiwea; Achmad Selamet Aku; Rahim Aka; Deki Zulkarnain (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
The need for beef in society continues to increase in line with national economic growth, increasing awareness of the importance of animal protein intake, population growth, and increasing purchasing power. Therefore, careful recording of information such as births, deaths, slaughter, production, sales, purchases, and imports of Bali cattle is crucial. This information is an important basis for evaluating and then increasing the productivity of Bali cattle. This research examines the natural increase in the Bali cattle population in Kabawo District, Muna Regency. This research was conducted from September to November 2022 in Kabawo District, Muna Regency. The variables observed in this research are the number of livestock population, birth rate percentage, death rate percentage, and natural increase value, and the data analysis used is descriptive analysis. The results of this research concluded that the birth rate of Bali cattle in the Kabawo District was 40.58%. In comparison, the death rate was 2.03%, and the percentage of natural increase was 38.55%, still better than in several other regions in Indonesia.